Inequalities in Smoking and Quitting-Related Outcomes Among Adults With and Without Children in the Household 2013–2019: A Population Survey in England. Issue 5 (11th October 2021) - Kock, Loren; Brown, Jamie; Shahab, Lion; Tattan-Birch, Harry; Moore, Graham; Cox, Sharon
Abstract: Introduction: Smoking among those who live with children is an important influence on smoking initiation among children. This study assessed socioeconomic inequalities in smoking and quitting-related outcomes among all adults with and without children in the household. Aims and Methods: Monthly repeat cross-sectional household survey of adults (16+) from 2013–2019 in England ( N = 138 583). We assessed the association between cigarette smoking and quitting-related outcomes and having children in the household, and whether these relationships were moderated by occupational social grade (categories AB–E from most to least advantaged). Trends in smoking prevalence among adults with and without children in the household were explored. Results: In adjusted analysis, the association of having children in the household with smoking prevalence depended on social grade: smoking prevalence was between 0.71 (95% confidence interval 0.66–0.77) and 0.93 (0.88–0.98) times lower among social grades AB–D with children in the household relative to those without. Conversely, it was 1.11 (1.05–1.16) times higher among social grade E. Yearly prevalence declined similarly among those with and without children (both prevalence ratio: 0.98, 95% confidence interval 0.97–0.99). Motivation to stop smoking was higher among those with children than those without, but lower among disadvantaged than more advantaged groups. Social grades D–E had greater heavy smoking, but higher prevalence of past-month quit attempts. Conclusions: Among the most disadvantaged social grade in England, smoking prevalence was higher in those with children in the household than without. To attenuate future smoking-related inequalities, there is an urgent need to target support and address barriers to quitting and promote longer-term quit success. Implications: In the most disadvantaged occupational social grade, having children in the household was associated with higher smoking prevalence compared with not having children. This contrasts with all other social grades in which there was lower comparative smoking prevalence among those with than without children in the household. Without attention this disparity could exacerbate existing and future health inequalities related to smoking.